Contributions of Regional Transport Versus Local Emissions and Their Retention Effects During PM2.5 Pollution Under Various Stable Weather in Shanghai - He, Baoshan; Yu, Guangyuan; Zhang, Xin; He, Zhiyin; Wang, Qian; Liu, Qizhen; Mao, Jingbo; Zhang, Yan (Frontiers in Environmental Science, 2022)
Abstract:Understanding the formation and development processes of air pollution events is key to improving the urban air quality. In this study, the air pollution casesepisodes in stable synoptic conditions were selected to analyze the multi-phase evolution processes of heavy air pollution in Shanghai, a coastal city. The observation data and the WRF-CMAQ model were used to diagnose and simulate the pollution characteristics of the heavy pollution casesepisodes. The results showed that the transport and dilution characteristics of PM2.5 were different during autumn and winter in Shanghai as a receptor of pollution transport. The development of PM2.5 pollution events were divided into four stages: accumulation stage, stagnation stage, enhancement stage, and dilution stage. The accumulation stage was before the stable weather, and provided the foundations for the PM2.5 pollution. The stagnation stage was nighttime during the stable weather, in which the low wind speed and temperature inversion weakened regional transport and the dilution of PM2.5, which was defined as “retention effect”. The “retention effect” played a dominant role during the stagnation stage, accounting for 71.2% and 41.2% of total PM2.5 in winter and autumn case, respectively. The enhancement stage followed the stagnation stage, in which the newly regional transport imported due to stronger wind speed, accounting for 86.3% and 46.2% in winter and autumn casesepisodes, respectively. The dilution stage was after the whole stable weather, when meteorological conditions were beneficial for the PM2.5 dilution. Local emissions were dominant (63.0%) for the PM2.5 pollution in the autumn case but regional transport was dominant (81.3%) for the winter case. Therefore, preventing the heavy particulate pollution caused by the diverse stable weather calls for the suitable emission control in a regional scale. Our study also shows the simulation accuracy during stable weather needs be improved in future study.